Impact of Light Environment on Driver's Physiology and Psychology in Interior Zone of Long Tunnel - Peng, Li; Weng, Ji; Yang, Yi; Wen, Huaiwei (Frontiers in Public Health, 2022)
In tunnels, lighting not only affects visual performance, but also non-visual aspects such as drivers’ physiological fatigue and mental stress. The non-visual impacts in the interior zone of long tunnels are particularly prominent as drivers are confined for a long time. To alleviate this problem, this study aims to investigate the relationship between drivers’ physiological and psychological states and lighting environments. The physiological signal test system (MP150) breathing belt was used to record the changes of heart rate variability (HRV) of drivers when passing through the interior zone of a long tunnel under various lighting conditions. In particular, sympathetic indicators of physiological fatigues and the ratio of low frequency and high frequency (LF/HF) representing mental load were obtained. By analyzing the temporal variation of these two indicators, it is found that environmental luminance perception can more accurately reflect drivers’ physiological and psychological states in the long tunnel than road luminance. An increase in road luminance or background luminance will result in a decrease in the mental stress, thereby reducing fatigue sense. Compared to simply increasing road luminance, mental stress of drivers decreased more obviously when the background luminance of long tunnel increased. On this basis, this paper proposed a method to regulate non-visual effect by adding contour markers without increasing light source intensity for the improvement of lighting performance, driving safety and energy efficiency in long tunnels.